Prevention And Handling Of Demonstrations In A Student City - Kurnia Ali Syarif; Andi Kasmawati; Ririn Nurfaathirany Heri (Cita konsultindo, 2024)
This research aims to obtain an overview of the police's strategy in handling student demonstrations in the city of Makassar which always carry out acts of anarchy. This research method is qualitative research, namely research that produces discoveries that cannot be achieved using statistical procedures or qualitative methods. The concept of this research is to obtain data or information related to police strategies in handling demonstrations in the city of Makassar. The police have an important role in the process of handling demonstrations carried out by citizens because they are tasked with protecting, maintaining security and public order. From the data obtained, the researcher analyzed descriptively qualitatively. From this data analysis, the researcher was able to formulate research results and draw conclusions, then prepare a report on the research results. Based on the results of research conducted by researchers regarding police strategies in handling student demonstrations in the city of Makassar, overall it can be concluded that The police's efforts in handling demonstrations in the green zone which were handled by the initial dalmas were providing security, guarding and acting as negotiators.